A Randomized Phase II Trial (TAMIGA) Evaluating the Efficacy and Safety of Continuous Bevacizumab Through Multiple Lines of Treatment for Recurrent Glioblastoma. (28th September 2018) - Brandes, Alba A.; Gil‐Gil, Miguel; Saran, Frank; Carpentier, Antoine F.; Nowak, Anna K.; Mason, Warren; Zagonel, Vittorina; Dubois, François; Finocchiaro, Gaetano; Fountzilas, George; Cernea, Dana Michaela; Chinot, Oliver; et al.
Abstract: Background: We assessed the efficacy and safety of bevacizumab (BEV) through multiple lines in patients with recurrent glioblastoma who had progressed after first‐line treatment with radiotherapy, temozolomide, and BEV. Patients and Methods: TAMIGA (NCT01860638) was a phase II, randomized, double‐blind, placebo‐controlled, multicenter trial in adult patients with glioblastoma. Following surgery, patients with newly diagnosed glioblastoma received first‐line treatment consisting of radiotherapy plus temozolomide and BEV, followed by six cycles of temozolomide and BEV, then BEV monotherapy until disease progression (PD1). Randomization occurred at PD1 (second line), and patients received lomustine (CCNU) plus BEV (CCNU + BEV) or CCNU plus placebo (CCNU + placebo) until further disease progression (PD2). At PD2 (third line), patients continued BEV or placebo with chemotherapy (investigator's choice). The primary endpoint was survival from randomization. Secondary endpoints were progression‐free survival in the second and third lines (PFS2 and PFS3) and safety. Results: Of the 296 patients enrolled, 123 were randomized at PD1 (CCNU + BEV, n = 61; CCNU + placebo, n = 62). The study was terminated prematurely because of the high drop‐out rate during first‐line treatment, implying underpowered inferential testing. The proportion of patients receiving corticosteroids at randomization was similar (BEV 33%, placebo 31%). For the CCNU + BEV and CCNU + placebo groups, respectively, median survival from randomization was 6.4 versus 5.5 months (stratified hazard ratio [HR], 1.04; 95% confidence interval [CI], 0.69–1.59), median PFS2 was 2.3 versus 1.8 months (stratified HR, 0.70; 95% CI, 0.48–1.00), median PFS3 was 2.0 versus 2.2 months (stratified HR, 0.70; 95% CI, 0.37–1.33), and median time from randomization to a deterioration in health‐related quality of life was 1.4 versus 1.3 months (stratified HR, 0.76; 95% CI, 0.52–1.12). The incidence of treatment‐related grade 3 to 4 adverse events was 19% (CCNU + BEV) versus 15% (CCNU + placebo). Conclusion: There was no survival benefit and no detriment observed with continuing BEV through multiple lines in patients with recurrent glioblastoma. Implications for Practice: Previous research suggested that there may be value in continuing bevacizumab (BEV) beyond progression through multiple lines of therapy. No survival benefit was observed with the use of BEV through multiple lines in patients with glioblastoma who had progressed after first‐line treatment (radiotherapy + temozolomide + BEV). No new safety concerns arose from the use of BEV through multiple lines of therapy. Abstract : This article focuses on the efficacy and safety of bevacizumab through multiple lines in patients with recurrent glioblastoma who progressed after first‐line treatment with radiotherapy, temozolomide, and bevacizumab.